Predominance of fetal malformations among pregnant women: A multi-centric observational study - Sayed, Sayed Mohamed; Khalifa, Ahmed Khedr; Abd Allah Shehata, Nesreen Abd El Fattah; Eweis , Mohamed AM; Shawky, Sherwet M (Clinical Journal of Obstetrics and Gynecology, 2021)
Objective: To observe the predominance of fetal anomalies in pregnant women in a multi-centric setting. Methods: This prospective observational study included 20225 pregnant women who came for antenatal care in University Hospital and fetal medicine units from 2016 to 2019. Fetal anatomical scanning was done for all participants. Results: One hundred eighty-three cases had fetal congenital anomalies, yielding a prevalence of around 0.9%. Third of cases had positive consanguinity, this increased in cases of skeletal and thoracic anomalies. The presence of past history of anomalies was evident in 8.2% mostly with skeletal and heart anomalies. History of drug intake was only verified in 1.6% of cases. Sixty-three women out of 183 (34.4%) were diagnosed to have anomalies in fetal nervous system. Conclusion: Prenatal diagnosis are recommended for early detection of congenital anomalies and counselling.